Analisis Keamanan Sistem Informasi Menggunakan Cobit 2019 pada Sistem Sawit Rakyat Online (SRO) Studi Kasus PTPN V - Arifin, Hanifan; Angraini, Angraini; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah (Program Studi Teknik Informatika Universitas Pamulang, 2024)
One of the businesses that utilise information technology (IT), especially at PTPN V, is using the Sawit Rakyat Online (SRO) system, which is used to buy and sell oil palm seeds online. The SRO system has previously been attacked by malware. And there is also no related security for users and the system. Thus the need for Information System Security Analysis Using Cobit 2019 on the SRO System. 2019 COBIT framework is one of the frameworks used to analyse information system security in an organisation. Data collection through interviews and questionnaires with stakeholders, as well as data evaluation using the 2019 COBIT Framework used in this study, especially the DSS (Deliver, Service, and Support) area, with a focus on subdomain DSS05 (manage security services). The goal is to find out how secure the actual handling of the SRO information system at PTPN V is. This research looks at how secure the Sawit Rakyat Online (SRO) information system is at PT Perkebunan Nusantara V (PTPN V). This shows that DSS05.01 and DSS05.02 are at level 5, namely